Peran Technopreneurs dalam Komersialiasi Teknologi Konverter Kit Motor Listrik (Studi Kasus: PT. EKM) - Muhammad Iqbal Sulistyo Putra; Wafiq Hasan Al Banna; Sayyidah Maulidatul Afraah; Yuniaristanto Yuniaristanto; Eko Liquiddanu; Wahyudi Sutopo (Universitas Mercu Buana, 2022)
Most of the technology from universities (PT) related to technological innovation often fails to enter the market. This problem then becomes the basis and object of improvement in technology-based entrepreneurial practices (technopreneurs). Learning is carried out through Independence Learning Campus Independence (MBKM) which converts courses according to training subjects in collaboration with PUI UNS and BPPT. This practice is a model of participatory and collaborative learning, in which students are directly involved in solving existing case studies and act as perpetrators of technology commercialization and become technopreneurs. Students are initially given training materials in accordance with the curriculum and direct learning from existing tenants. As a result, through this learning process, students can design business process proposals that exist in tenants. The success of this learning method was assessed based on technopreneur analysis from students in answering problems faced by tenants based on aspects of product technology innovation, product development, business development, and its implementation at BMC. One of the tenants who is the object of the case study in this study is the start-up PT. EKM who have problems with the commercialization of technology in the case of konverter kit products.